2014
DOI: 10.4236/ojog.2014.415132
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Extracellular Matrix and Cytokines after Uterine Artery Embolization

Abstract: Arterial embolization of myomas (AEM) is an established option for the conservative treatment of uterine leio-myomas; it treats all present uterine nodules at once, is less invasive than other procedures and effective in controlling symptoms, and does not require long term hospitalizations. Nevertheless, the potential impact on endometrial morphological and functional outcomes after the procedure is still controversial based on reports of endometritis or eventual transient ischemia. This study evaluated endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The metalloproteinase genes are related to the facilitation of embryonic implantation ( 7 , 8 , 10 , 16 ). In our study, we observed an under-expression of MMP3 6 months post-AEM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metalloproteinase genes are related to the facilitation of embryonic implantation ( 7 , 8 , 10 , 16 ). In our study, we observed an under-expression of MMP3 6 months post-AEM.…”
Section: Discussionmentioning
confidence: 99%
“…ECM metalloproteinases (MMP) are involved in matrix rupture during physiological processes such as embryonic development, reproduction, and tissue remodeling. Degradation and remodeling of the ECM are also key events in human reproduction ( 9 , 10 ). Hilario et al ( 11 ) evaluated gene expression related to endometrial receptivity in patients undergoing AEM, concluding that there was under-expression of the LIF , IL-11 , and Hoxa-11 genes, and that the expression of IL-6, claudin-4, Hoxa-10, estrogen, and progesterone receptors in the endometrium did not change significantly after AEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation